A comparison characteristic on wood charcoal combustion in different wood species - DONSAVANH, Beun; PHETHDONEMO, Phaivanh; CHANNANG, Bounheuang; PHONCHALUEN, Sengkham; BOUAPHAKEO, Pazeun (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
A study on characteristics of wood charcoal combustion focuses on the time of fire appearing and burned, the temperature during firing, and ash after burning of the four groups of wood charcoal species, including Earleaf acacia, Teak, Bamboo, and Mixed Wood Charcoal from different market. The objective was to measure about characteristics of wood charcoal combustion time in a minute, the temperature in Celsius degree, and ash in grams with three samples of wood charcoal such as Earleaf acacia, Teak, and Bamboo by the gasifier system with a metal tank 200 liters and one that is mixed wood charcoal from the market. In addition, the experiment collects quantitative measurement data to analyze descriptive statistics and One-Way ANOVA (Analysis of variance) for the result in different significant statistics. As a result, the four groups of wood charcoal combustion were weight averages of 297.50 grams to measure the value of time, temperature, and ash of Earleaf acacia, Teak, Bamboo, and mixed charcoal. The time of fire appearance spent about 2.66, 3.00, 4.66, and 4.25 minutes, followed by a time of burned of 65.66, 57.33, 60, and 65.25 minutes, respectively. Moreover, this research found that the temperature during burned of wood charcoal were about 677.67, 649.57, 557.86, and 647.02 Celsius degree, respectively. Part of the ash of wood charcoal in four groups were 5.13, 15.01, 17.85, and 9.50 percent, separately. Importantly, the study on characteristics of wood charcoal in different plant species tested temperature during burning by One-Way ANOVA, found that the charcoal of bamboo was significant at p-value value ≤ 0.05 and p-value ≤ 0.01, implying that the bamboo charcoal is significantly different from the temperature in Celsius degree between Earleaf acacia, Teak, and mixed charcoal, this research found additionally significant in statistic at p-value ≤ 0.05 and P-value ≤ 0.01 between the Earleaf acacia and Teak. As a result, this study showed the importance of the diversity of woody plants and bamboo properties for charcoal combustion, they are especially the time and temperature of combustion of Earleaf acacia, and Teak, which are properly tree growth for plantation and these trees’ species can grow rapidly, and it is releasing heat of combustion in the same level. Lastly, the organization involvement should promote the Earleaf acacia, and Teak for wood supply in terms of energy to farmers and entrepreneurs.